Items of Yamaguchi Criteria Might be Associated with Disease Severity and Prognosis in Adult-Onset Still's Disease - Kalyoncu, Umut; Solmaz, Dilek; Emmungil, Hakan; Yazici, Ayten; Kasifoglu, Timucin; Kimyon, Gezmis; Pay, Salih (Wiley, 2015)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology (ACR) and Association-of-Rheumatology-Health-Professionals (ARHP) -- NOV 06-11, 2015 -- San Francisco, CA